Comprehensive review of mapping climate change impacts on tea cultivation: bibliometric and content analysis of trends, influences, adaptation strategies, and future directions - Ali Abaker Omer, Altyeb; Zhang, Chun-Hua; Liu, Jie; Shan, Zhi-guo (Frontiers in Plant Science, 2025)
Climate change has a profound impact on tea cultivation, posing significant challenges to yield, quality, and sustainability due to stressors such as drought, temperature fluctuations, and elevated CO₂ levels. This study aims to address these challenges by identifying and synthesizing key themes, influential contributions, and effective adaptation strategies for mitigating the impacts of climate change on tea production. A systematic bibliometric and content analysis was conducted on 328 peer-reviewed documents (2004–2023), following the PRISMA methodology. Performance analysis using Bibliometrix examined trends in publication output, leading contributors, and geographical distribution, while science mapping with VOSviewer revealed collaboration networks and thematic clusters. A detailed review of highly cited studies highlighted the primary climate variables affecting tea cultivation and identified innovative adaptation strategies, as well as critical knowledge gaps. The results show significant progress in understanding the physiological, biochemical, and molecular responses of tea plants to climate-induced stressors, including antioxidant mechanisms, secondary metabolite regulation, and genomic adaptations. Despite these advancements, challenges remain, particularly regarding the combined effects of multiple stressors, long-term adaptation strategies, and the socioeconomic implications of climate change. The findings underscore the need for interdisciplinary approaches that integrate molecular, ecological, and socioeconomic research to address these issues. This study provides a solid foundation for guiding future research, fostering innovative adaptation strategies, and informing policy interventions to ensure sustainable tea production in a changing climate.